Building Better Bridges: Toward a Transdisciplinary Science Communication. Issue 2 (3rd April 2019) - Johnson, Jenell; Xenos, Michael A.
ABSTRACT: In this article the authors envision a more durable and portable model of scholarship on public engagement with science through partnerships between rhetoricians of science and quantitative social scientists. The authors consider a number of barriers and limitations that make such partnerships difficult, with an eye toward discovering ways that researchers may overcome them. The authors conclude by articulating guidelines for reciprocal transdisciplinary work as well as specific recommended practices for such collaborations.